Influence of Research Self-efficacy on Research Productivity of Academic Staff in Private Universities in Oyo State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Academic staff members of university are the key to productive research outcome in many nations of the world and they determine the outcome of research direction whether productive or not. It is in the light of this that this study therefore deems it fit to investigate the role of research self-efficacy on research productivity of Academic Staff in Private Universities in Oyo State. Descriptive research design of a correctional type was adopted. The population consists of 717 academic staff in private universities in Oyo state, Nigeria. Sample size of 255 academic staff was determined using Yamane table of sampling size, while validated questionnaire was used to collect data from the respondents. Data collected was analyzed using descriptive and inferential statistics. Findings revealed that research self-efficacy has significant influence on research productivity (Adj.R2 = 0.104; p = 0.000). Jointly, Research self-efficacy was found to statistically significantly influence Research Productivity Adj.=.112, F(2,,252)=17.010, p < 0.05,. The study concluded that Research Self-efficacy influenced Research Productivity. The study recommended that academic staff in private universities should work and improve on their research skills such as identifying research gaps, reviewing literature extensively, following the ethical principles of research and many more.